2008
DOI: 10.1074/jbc.m708341200
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans K10C2.4 Gene Encodes a Member of the Fumarylacetoacetate Hydrolase Family

Abstract: In eukaryotes and many bacteria, tyrosine is degraded to produce energy via a five-step tyrosine degradation pathway. Mutations affecting the tyrosine degradation pathway are also of medical importance as mutations affecting enzymes in the pathway are responsible for type I, type II, and type III tyrosinemia. The most severe of these is type I tyrosinemia, which is caused by mutations affecting the last enzyme in the pathway, fumarylacetoacetate hydrolase (FAH). So far, tyrosine degradation in the nematode Cae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 55 publications
6
69
0
Order By: Relevance
“…The HGO, an enzyme upstream of FAH in the Tyr degradation pathway, is essential for the catalysis of homogentisate into MAA and FAA (Lindblad et al, 1977). Inactivation of HGO in fungi, mice, and worms, therefore, was able to rescue the lethality associated with FAH mutations (Fernández-Cañón and Peñalva, 1995b;Manning et al, 1999;Fisher et al, 2008). Through generation of the double mutant sscd1 hgo, we also found that disruption of the Arabidopsis putative HGO is able to completely eliminate the spontaneous cell death in the sscd1 mutant (Fig.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The HGO, an enzyme upstream of FAH in the Tyr degradation pathway, is essential for the catalysis of homogentisate into MAA and FAA (Lindblad et al, 1977). Inactivation of HGO in fungi, mice, and worms, therefore, was able to rescue the lethality associated with FAH mutations (Fernández-Cañón and Peñalva, 1995b;Manning et al, 1999;Fisher et al, 2008). Through generation of the double mutant sscd1 hgo, we also found that disruption of the Arabidopsis putative HGO is able to completely eliminate the spontaneous cell death in the sscd1 mutant (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…In both human HT1 and mouse fah mutants, the metabolic intermediates (MAA, FAA, succinylacetoacetate, and succinylacetone) were highly accumulated, which are toxic to cells and tissues (Lindblad et al, 1977;Grompe et al, 1993;Aponte et al, 2001;Jorquera and Tanguay, 2001). Due to technical difficulties, it is so far not possible to detect these metabolic intermediates in entire worms (Fisher et al, 2008) and in Arabidopsis plants (data not shown). To verify that the cell death phenotype in the sscd1 mutant might also have resulted from the accumulation of succinylacetoacetate and succinylacetone, we followed the approach used in worms (Fisher et al, 2008) and treated Arabidopsis seedlings with succinylacetone, the unique product that is commercially available among these metabolic intermediates.…”
Section: Succinylacetone Induces Cell Death In Arabidopsismentioning
confidence: 99%
See 1 more Smart Citation
“…This can lead to the construction of a transgene which is more reflective of the native expression pattern, or the construction of a functional transgene when other approaches fail 5 . The resulting transgenes can carry a variety of epitope tags including GFP or a TAP tag.…”
Section: Discussionmentioning
confidence: 99%
“…While these transgenes are often successful with regards to producing a GFP reporter gene or expressing a cDNA in a desired pattern, these transgenes can lack the alternate promoters, enhancer elements, and 3' untranslated region (UTR) elements which play important roles in the control of gene expression in vivo 2 . For example, both the daf-12 and fah-1 genes have important enhancer elements which lie outside of the proximal promoter which were missed in promoter only constructs 3,4,5 . Further many transgene constructs use the unc-54 3'UTR which prevents regulation by the appropriate microRNA genes 6,7,8 .…”
Section: Overviewmentioning
confidence: 99%